1965
DOI: 10.3171/jns.1965.23.1.0076
|View full text |Cite
|
Sign up to set email alerts
|

Intraneural Cyst of the Peroneal and Ulnar Nerves

Abstract: Intraneural cyst is a rare lesion. Probably the earliest case was that of Hartwell 4 reported in 1901. The patient had a mass the size of a chestnut on the medial aspect of the arm just above the elbow and at operation it was found to be a cystic tumor involving the median nerve. The contents of such a cyst may be semigelatinous in consistency and result from mucoid degeneration of a schwannoma or a neurilemmoma. An intraneural cyst should not be mistaken for a ganglion which may by proximity cause compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
7

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 2 publications
0
30
0
7
Order By: Relevance
“…In our literature review of upper extremity intraneural ganglions, we have found that the time from symptomatic presentation to surgery for complete to nearcomplete recovery ranged from as little as 4 weeks to more than 1 year [1,4,8,10,13,15]. Incomplete or moderate recovery was found in patients symptomatic for 8 months and 2 years [1,5]. In the two cases of little to no recovery after complete excision, one patient was symptomatic for only 2 months [1] and the other for 6 months [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our literature review of upper extremity intraneural ganglions, we have found that the time from symptomatic presentation to surgery for complete to nearcomplete recovery ranged from as little as 4 weeks to more than 1 year [1,4,8,10,13,15]. Incomplete or moderate recovery was found in patients symptomatic for 8 months and 2 years [1,5]. In the two cases of little to no recovery after complete excision, one patient was symptomatic for only 2 months [1] and the other for 6 months [2].…”
Section: Discussionmentioning
confidence: 99%
“…All of the cited reports of intraneural ganglion of the ulnar nerve at the level of the wrist [1,5,9,10,15] involved the deep branch of the ulnar nerve. Our presented case involved a similar ganglion, found in the deep motor branch of the ulnar nerve, just below the level of the hypothenar muscles.…”
Section: Discussionmentioning
confidence: 99%
“…[3, 5-16, 18, 20-24, 26, 1, 2, 17] Since the first description of ganglia involving nerves, [8] most reported cases concern the common peroneal nerve at the head of the fibula. [6,15,16,18,22,23,26] The compression of the ulnar nerve in the cubital tunnel by a ganglion is not common. [5,10] In addition, most ganglion cysts involving nerves originate from the adjacent joints.…”
Section: Discussionmentioning
confidence: 99%
“…The capsular defect may be preexisting and is likely the result of a traumatic, degenerative, or congenital process. 11,44,45 In the peroneal intraneural ganglia model, evidence suggests that direct or indirect cumulative trauma 13,14,20,44 to the superior tibiofibular joint itself or in relation to the neighboring (and often communicating) knee joint is important in the development of the cysts. 45 Increased intraarticular pressure (that is, static or dynamic) is the other mechanism involved at the jointjoint capsule interface.…”
Section: Joint-joint Capsule Interfacementioning
confidence: 99%
“…Different theories, without a scientific basis, have been proposed. 4,[6][7][8]15,19,20,24,27 The articular (synovial) theory, 42,45 based on robust clinical, imaging, and histological evidence, 11,[39][40][41][42]44,45,47,49,50 provides a logical, consistent explanation that clarifies and unifies the observations made by many over the years. Developed on the prototype of the peroneal nerve ganglion cysts, the theory can be extrapolated to intraneural ganglion cysts involving other nerves.…”
mentioning
confidence: 99%